Genetic landscape of Rett syndrome-like phenotypes revealed by whole exome sequencing. Issue 6 (6th March 2019) - Iwama, Kazuhiro; Mizuguchi, Takeshi; Takeshita, Eri; Nakagawa, Eiji; Okazaki, Tetsuya; Nomura, Yoshiko; Iijima, Yoshitaka; Kajiura, Ichiro; Sugai, Kenji; Saito, Takashi; Sasaki, Masayuki; Yuge, Kotaro; et al.
Abstract : Background: Rett syndrome (RTT) is a characteristic neurological disease presenting with regressive loss of neurodevelopmental milestones. Typical RTT is generally caused by abnormality of methyl-CpG binding protein 2 ( MECP2 ). Our objective to investigate the genetic landscape of MECP2 -negative typical/atypical RTT and RTT-like phenotypes using whole exome sequencing (WES). Methods: We performed WES on 77 MECP2 -negative patients either with typical RTT (n=11), atypical RTT (n=22) or RTT-like phenotypes (n=44) incompatible with the RTT criteria. Results: Pathogenic or likely pathogenic single-nucleotide variants in 28 known genes were found in 39 of 77 (50.6%) patients. WES-based CNV analysis revealed pathogenic deletions involving six known genes (including MECP2 ) in 8 of 77 (10.4%) patients. Overall, diagnostic yield was 47 of 77 (61.0 %). Furthermore, strong candidate variants were found in four novel genes: a de novo variant in each of ATPase H + transporting V0 subunit A1 ( ATP6V0A1 ), ubiquitin-specific peptidase 8 ( USP8 ) and microtubule-associated serine/threonine kinase 3 ( MAST3 ), as well as biallelic variants in nuclear receptor corepressor 2 ( NCOR2 ). Conclusions: Our study provides a new landscape including additional genetic variants contributing to RTT-like phenotypes, highlighting the importance of comprehensive genetic analysis.